In-situ preparation of silk-cocoon derived carbon and LiFePO4 nanocomposite as cathode material for Li-ion battery. Issue 23 (1st December 2022) - Gangaraju, Vinay; Shastri, Mahesh; Shetty, Krushitha; Marilingaiah, Navya Rani; K.S., Anantharaju; Doddakunche Shivaramu, Prasanna; Rangappa, Dinesh
Abstract: We report a natural fiber template method for the synthesis of lithium iron phosphate carbonized silk cocoon (LFP-CS), as cathode electrode material for lithium-ion batteries. Bombyx-mori silk-cocoons was used as template and heated along with LFP precursor to obtain a carbonized silk carbon network around LFP. The X-ray powder diffraction (XRD) shows a well crystalline single-phase olivine structured LFP-CS nanoparticle. Scanning electron microscope (SEM) and Transmission electron microscopy (TEM) revealed the spherical morphology of LFP nanoparticle, which was absorbed on the surface and sub-surface of the cocoon fibers. The LFP nanoparticles were uniformly dispersed within the layer of carbon sheet, forming conductive carbon network between individual particles. The electrochemical study revealed that the LFP-CS has a capacity of 163 mAh/g at 0.1C and 123 mAh/g at 5C rate with excellent cycle performance. Apparently, conductive carbon network formed could also increase the electrochemical performance of the electrode material.